Effect of Repetitive Transcranial Magnetic Stimulation According to the Stimulation Site in Stroke Patients With Dysphagia - Lee, Jong Hwa (Ann Rehabil Med, 2015)
OBJECTIVE: To investigate the effect of repetitive transcranial magnetic stimulation (rTMS) according to the stimulation site in subacute stroke patients with dysphagia. METHODS: This study was designed as a matched comparative study. Twenty-four patients who had dysphagia after ischemic stroke were recruited, and they were divided into two groups after matching for age and stroke lesion. The patients in group A received rTMS over the brain cortex where motor evoked potential (MEP) was obtained from the suprahyoid muscle. Group B received rTMS over the brain cortex where MEP was obtained from the abductor pollicis brevis muscle. rTMS was performed at 110% of MEP threshold, 10 Hz frequency for 10 seconds, and then repeated every minute for 10 minutes. Dysphagia status was measured by the Functional Dysphagia Scale (FDS), the Penetration-Aspiration Scale (PAS), and the Dysphagia Outcome and Severity Scale (DOSS) using the results of a videofluoroscopic swallowing study. These evaluations were measured before, immediately, and 4 weeks after rTMS. RESULTS: Group A showed significant improvement compared to group B in the DOSS score immediately and 4 weeks after rTMS. There were no significant differences in the changes of FDS and PAS scores between groups A and B immediately and 4 weeks after rTMS. CONCLUSION: rTMS over a hot spot for the suprahyoid muscle caused more improvement in swallowing function when compared to that over the interconnected site.